Shaping Ideologies of the Good(s) Life: How Mass-Mediated Marketplace Ideologies Shape and Reflect Consumption Ideologies - Nyman, Jannica (United States, 2025)
This paper examines the role of mass-mediated marketplace ideologies in shaping and reflecting consumption ideologies. It utilizes Consumer Culture Theory (CCT) as a metatheoretical lens to synthesize fragmented literature across disciplines and construct a conceptual framework detailing this interplay. Addressing three research questions, the study identifies previous theoretical frameworks to describe the relationship in marketing literature, describes dimensions of mass media and consumption ideologies' interrelation, and pinpoints gaps and contradictions in current research. The findings reveal how mass-mediated marketplace ideologies contribute to the persistence of the attitude-behavior gap. This review stresses the need for enhanced media literacy and proposes that understanding media's influential role is key to addressing sustainable and ethical consumption practices. The paper concludes with suggestions for future research that could further illuminate the mechanisms of consumer culture and media’s impact on consumer agency.
Proceedings of the 49th Annual Macromarketing Conference